Systematic Red Volchanka (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Rheumatoid disease is a disease of unknown etiology (idiopathic) with damage to systems and organs due to an antigen-antibody complex. SQV is an autoimmune disease, and one of the main causes of clinical symptoms is the deposition of antinuclear immune complexes in tissues and basement membranes formed by antibodies with binding parts of cell nuclear elements (DNA, RNA, histones). In addition, cell fragments that die with apoptosis, increased netosis, and reduced autophagy become targets of immune system cells. Immune complexes enter plasmacytoid dendritic cells through FcyRIIa receptors, then nucleic acids of immune complexes activate interferon receptors. In this way, activated interferons (IFN -α) begin to be produced in abundance. These cytokines, in turn, produce autoreactive antibodies by monocytes and Betta cells. The production of monocytes, neutrophils and dendritic cells increases under the influence of type I IFN. All this leads to an increase in the number of immune complexes.